Capacity Building on BSB Organic Development Center - Winarko, Hilarius Bambang; Fitriningrum, Andriati; Wahyuni, Maria Josef Retno Budi; Pulungan, Andrey Hasiholan (Center for Research and Community Service of Sampoerna University, 2021)
This community service project was aimed to scale up Bina Sarana Bhakti (BSB) organic development center’s management with two-day workshops. BSB needs to improve its managerial skills and knowledge in-order able to transform its business in a more profitable way. Agile leadership with good communication approach and human capital plays important role in-order BSB able to keep in the right track and sustainable in facing fierced market competitions and future uncertainty.